Electrodeposited cobalt-copper sulfide counter electrodes for highly efficient quantum dot sensitized solar cells. (20th August 2016) - Givalou, Lida; Antoniadou, Maria; Perganti, Dorothea; Giannouri, Maria; Karagianni, Chaido-Stefania; Kontos, Athanassios G.; Falaras, Polycarpos
Abstract: A series of novel composite Cobalt-Copper Sulfide (CoS-CuS) counter electrodes were developed for Quantum Dot Sensitized Solar Cells (QDSSCs) based on core-shell cadmium sulfide-cadmium selenide quantum dots. The new electrodes were prepared by one-step electrodeposition from an aqueous solution containing cobalt chloride (CoCl2 ·6H2 O), copper chloride (CuCl2 ·2H2 O) and thiourea. The composite electrodes present rough morphology consisting of CuS agglomerates on a CoS continuous nanowire network, allowing easy electron transfer across the CE-electrolyte interface. The corresponding QDSSCs demonstrate power conversion efficiencies (PCE) exceeding 5%, under one sun illumination. By increasing the mesoporous layer thickness, adding a scattering layer and adjusting the QDs deposition conditions, a PCE as high as 7.49% was obtained. These very promising results further justify and account for the innovative character of the composite CoS-CuS counter electrodes.